Law Enforcement through Justice and Ethical Institution: Historical Perspective - Aisyah, Siti; Ismail, Nurizal (University of Darusssalam Gontor, 2018)
Islam is the way of life which guides mankind to attain the happiness in here and thehereafter (falah). It is also a religion of peace through the submission to the will and laws ofGod, advocates the establishment of ethic and social justice in order to achieve peace. In thehistory of Islam, enforcement of law was implemented to preserve good ethic and justice in thesociety. Therefore, it is needed to know how the implementation of Islamic law enforcementregarding ethic and justice in Islamic framework. This paper aims to study how the Islamicstate in the early of Islam pays attention to ethic and justice of society in its governmentaffair or administration and how the wilāyat al mazālim and hisbah as Islamic institutionwill stand for law enforcement to promote justice and higher ethic in the society. Moreover,finding of the study states that the Justice and ethical values have been still concerned byIslamic State. The administration of justice carried out by Muslim should consist of theapplication of Shari’ah in name of God without any temporal consideration. Enforcementof law regarding ethic and justice is manifested in hisbah and wilāyat al-mazālim. Eachinstitution has different duties, but has mutual relation to administrate the state towardwelfare state. The hisbah institution plays its role to command good action (amar ma’ruf)and prohibit evil (nahi munkar). It has a responsible for the implementation of Shari’ahprinciples in society. Furthermore, wilāyat al-mazālim is an institution that carries out thejustice around the society. This institution looks into the cases which are not included incommon court authority, such as persecution matters which are committed by the authority,judges or member ruling family.